2011
DOI: 10.2105/ajph.2010.200915
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Poor Oral Health on Children's School Attendance and Performance

Abstract: Children with poorer oral health status were more likely to experience dental pain, miss school, and perform poorly in school. These findings suggest that improving children's oral health status may be a vehicle to enhancing their educational experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
364
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(404 citation statements)
references
References 21 publications
13
364
1
12
Order By: Relevance
“…Dental caries are 5 times more prevalent than asthma among children ages 5 to 17 years, 1 lowincome children are at a particularly high risk of poor oral health, [1][2][3][4] and poor oral health is associated with chronic pain and diminished quality of life. [5][6][7] Untreated dental caries can result in complications leading to emergency department (ED) visits for pediatric dental care and inpatient admissions. 8 Conventional wisdom among the dental and public health communities presumes that preventive dental care is "the cornerstone of optimal oral health promotion," 9 that such preventive dental care is cost-effective, 10 and that timely preventive and restorative services can reduce the need for the considerably more expensive ED or inpatient treatment of dental problems.…”
Section: Resultsmentioning
confidence: 99%
“…Dental caries are 5 times more prevalent than asthma among children ages 5 to 17 years, 1 lowincome children are at a particularly high risk of poor oral health, [1][2][3][4] and poor oral health is associated with chronic pain and diminished quality of life. [5][6][7] Untreated dental caries can result in complications leading to emergency department (ED) visits for pediatric dental care and inpatient admissions. 8 Conventional wisdom among the dental and public health communities presumes that preventive dental care is "the cornerstone of optimal oral health promotion," 9 that such preventive dental care is cost-effective, 10 and that timely preventive and restorative services can reduce the need for the considerably more expensive ED or inpatient treatment of dental problems.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 16% of children living in poverty were reported by a parent to have had a toothache within the last 6 months (3). A recent multivariate analysis also found that children with poor oral health miss more school days and receive lower grades than children with good oral health (4).…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral health affects quality of life as a result of pain or discomfort, tooth loss, impaired oral functioning, disfigurement, missing school time, loss of work hours and even death (in the case of oral cancers). Oral health also has an effect on many chronic diseases (2)(3)(4)(5). Although oral health in many countries has improved considerably in recent decades, with a declining trend of dental caries, it appears to be showing a rising trend, especially in developing countries, thus widening inequities in oral health (6)(7)(8) Reducing such inequalities in health has become a major focus for government health policy (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%